2022
DOI: 10.1155/2022/1447388
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Nursing Effect of Health Monitoring System on Elderly Patients with Osteoporosis

Abstract: Health monitoring can provide scientific and reasonable care for elderly users, professionally monitor the health parameters of the human body, and timely understand the user's own physical condition. By installing sensors with different functions in the rooms where the elderly often move and by installing vital signs sensors on their bodies, the data detected by the sensors are collected and analyzed in real time. Nursing refers to the fact that nursing staff must strictly follow the nursing system and operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The incidence of osteoporosis and osteoporotic fractures can be reduced by improving nursing care for osteoporosis ( 270 ). First, we should strengthen the publicity and education on osteoporosis and improve people’s awareness of preventative measures ( 271 ).…”
Section: Quality Of Life and Nursing Care Of Patients With Ra And Pmopmentioning
confidence: 99%
“…The incidence of osteoporosis and osteoporotic fractures can be reduced by improving nursing care for osteoporosis ( 270 ). First, we should strengthen the publicity and education on osteoporosis and improve people’s awareness of preventative measures ( 271 ).…”
Section: Quality Of Life and Nursing Care Of Patients With Ra And Pmopmentioning
confidence: 99%
“…A behavioural modification strategy that has shown effectiveness in addressing osteoporosis is self-management. Self-management, particularly when facilitated through smartphone APPs for osteoporosis prevention, typically involves activities such as goal setting, self-monitoring and adopting specific behaviours [94]. In addition to PA, maintaining a healthy diet, adhering to medication treatment and preventing falls are included in this approach, which is linked to changes in health behaviour [95].…”
Section: Self-management Of Osteoporosis: Telemedicine As An Optimal ...mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%